Development of A Modernized Tube For Determining The Speed And Pressure Of The Air Flow (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
A Modernized Tube For Determining The Speed And Pressure Of The Air FlowKhalilov M.S. Ph.D.,Karshi Engineering and Economic Institute Designed and manufactured a modernized trubka to determine the pressure and velocity of the air flow. made tube attached to the manometer MMN-246(5)of -1.0 and a study on verification in the device PAT No. 016 and dmts-01.M The State. Standard for determination of the pressure and Soroti air flow. Determined parameters of the devices PAT No. 016 and dmts-01.M (taken for reference) and manometer MMN-240(5)of -1.0. Based on the obtained data, we plot the analysis results. In devices PAT No. 016 and DMC-01 and MMN-240(5)of -1.0 the values of the correction ratios to determine the pressure "S" and velocity "D" of the air flow for each value of the coefficient K , taking into account the inclined installation of the pipe. The results of the calibration of manometer MMN-246(5)of -1.0 with the upgraded tube State. Standard "Uzhydrometcenter" issued certificate No. 170 (15,03,2017).